The Effect of Practical Experience, Knowledge of Job Opportunities, Teacher Professionalism and Work Motivation on Work Readiness - Darul Prayogo; Andy Wahyu Hermanto; F. Pambudi Widiatmaka; Dwi Prasetyo; Sugiyarto Sugiyarto (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The main problem faced by the education world is the low employment level for graduates of Vocational Senior High Schools (SMK). Ideally, there should be 80% to 85% graduates that should be directly admitted to the work forces, but up till now this percentage is approximately only 61%. The article analyze how the effect of Practical Experience, Knowledge of Job Opportunities, Teacher Professionalism and Work Motivation on Work Readiness at Vocational High School (SMK) Semarang Automotive mechanical expertise program. The research sample was taken using cluster proportional random sampling. Data were collected by questionnaires and documentation. Based on a preliminary test on grade XII students of Mechanical Automotive of SMK found that there were 36 valid problems and 18 invalid ones in the questionnaires. These problems were then refined and reduced proportionally to only 40 according to the existing sub-factors. After being e-tested the instrument produced a validity score higher that the table r (0.334). It meant that the instrument was valid and could be used as an appropriate tool for tests. The data were analyzed using percentage-descriptive analyses. The total effect of experiences in practices on the readiness of the students to enter the existing wok force was 2%, the total effect of students’ knowledge about employment was 3.04% and the total effect of teachers’ professionalism was 2.63%. Based on the above findings, it can be concluded that there were effects of experiences in academic practices, of students’ knowledge about the existing employment, of teacher professionalism and of students’ motivations for work on readiness to enter the work forces. Collectively, these four factors contributed 30.6% of the total effect, while the remaining 60.4% of the total effect was due to by some other factors not investigated in this research. Keywords: Practical Experience, Teacher Profesionalism, Work Readiness